Phosphite alters the behavioral response of potato tuber moth (Phthorimaea operculella) to field‐grown potato. Issue 3 (17th September 2018) - Mulugeta, Tewodros; Mulatu, Bayeh; Tekie, Habte; Yesuf, Mohammed; Andreasson, Erik; Alexandersson, Erik
Abstract: BACKGROUND: The potato tuber moth (PTM)( Phthorimaea operculella ) is a pest of solanaceous species that causes serious damage to potato tubers and tomato fruits. Control is mainly dependent on the use of synthetic chemicals, which pose a risk to the environment and health of farmers, especially in developing countries where application safety rules are often neglected. In this study we aimed at investigating the effects of a plant resistance inducer (PRI) potassium phosphite on PTM larval population density and PTM parasitoid levels, which can be used as biocontrol agents. We also tested whether intercropping with tomato, which is less attractive to PTM, provided a spatial border to further reduce PTM numbers. RESULTS: In two different locations over two seasons, we showed that foliar application of phosphite more than halved the PTM larval populations on potato, and that PTM parasitoid numbers were unaffected. No consistent reduction in PTM was achieved by intercropping potato with tomato. CONCLUSIONS: Phosphite reduced PTM numbers in the field without interfering with autochthonous parasitoids, indicating its suitability as part of an Integrated Pest Management strategy. Ex situ choice tests showed that phosphite‐treated potato deterred PTM, which could be a reason for the control of PTM in the field. © 2018 Society of Chemical Industry Abstract : Phosphite has received high attention as a low‐toxicity fungicide. We show that phosphite reduces field larval populations of potato tuber moth and changes the behavior of adult females.